Proceedings of Offshore Technology Conference 2009
DOI: 10.4043/otc-19912-ms
|View full text |Cite
|
Sign up to set email alerts
|

Extending Deepwater Technology to Seafloor Mining

Abstract: This paper builds on the experience of designing, and building production and drilling risers for oil and gas fields and extends into deepwater mining. With the recent discovery of high grade seafloor massive sulphides (SMS) in Papua New Guinea, New Zealand and elsewhere, there is a resurgence of interest in deep ocean mining. This renewal of interest has been spearheaded by Nautilus Minerals through its Solwara 1 project; in 1,700 m of water, with a production rate of 2.0 million tons per annum. Neptune Miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, the required amount of power to lift the minerals in 2500m water depth (with the same production rate) is less than 6MW [13]. Therefore, it can be concluded that approximately 1MW (14%) will be lost in the system especially by mechanical friction in the hydraulic feeding tubes to SSLP.…”
Section: Subsea Power Demand Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the required amount of power to lift the minerals in 2500m water depth (with the same production rate) is less than 6MW [13]. Therefore, it can be concluded that approximately 1MW (14%) will be lost in the system especially by mechanical friction in the hydraulic feeding tubes to SSLP.…”
Section: Subsea Power Demand Estimationmentioning
confidence: 99%
“…In addition to the ongoing research activities, a few companies have been working on this concept. Neptune Minerals is one of them that has designed a set of mining equipment including a grabber, an SMS crusher and a mining tool to extract the SMS minerals offshore New Zealand [13]. The airlift system is proposed by Neptune Minerals for vertical transportation [13].…”
Section: Deep-sea Mining Processmentioning
confidence: 99%
See 1 more Smart Citation